2017
DOI: 10.1111/petr.12881
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of pediatric living donor kidney transplantation: A single‐center experience

Abstract: Renal transplantation is the treatment of choice for children with ESRD offering advantages of improved survival, growth potential, cognitive development, and quality of life. The aim of our study was to compare the outcomes of LDKT vs DDKT performed in children at a single center. Retrospective chart review of pediatric patients who underwent kidney transplantation from 2005 to 2014 was performed. Ninety-one renal transplants were accomplished, and 31 cases (38.27%) were LDKT, and in 96.7% of the cases, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Given these considerations, pediatric recipient transplantation with adult donor kidneys is common, particularly so in living donor transplantations . The intraoperative management of adult donor pediatric recipient transplantations is delicate, especially for smaller recipients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these considerations, pediatric recipient transplantation with adult donor kidneys is common, particularly so in living donor transplantations . The intraoperative management of adult donor pediatric recipient transplantations is delicate, especially for smaller recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Given these considerations, pediatric recipient transplantation with adult donor kidneys is common, particularly so in living donor transplantations. 3 The intraoperative management of adult donor pediatric recipient transplantations is delicate, especially for smaller recipients. Surgery is technically challenging due to vessel size mismatch at anastomoses, and the donor organ and recipient patient have potentially divergent hemodynamic requirements.…”
mentioning
confidence: 99%
“…The renal transplantation at our center was from living donor, majority from LRD (parents). Living donor transplant is reported to have better survival outcomes for pediatric recipients irrespective of donor age and should be recommended whenever possible . Immunosuppression protocols followed at our center are in accordance with the current practices and guidelines followed across the world…”
Section: Discussionmentioning
confidence: 92%
“…Living donor transplant is reported to have better survival outcomes for pediatric recipients irrespective of donor age and should be recommended whenever possible. 13,17,18 Immunosuppression protocols followed at our center are in accordance with the current practices and guidelines followed across the world. 12,13 Most recipients in our study had a negative history of post-trans- The graft survival rates observed at our center were 96.7% probabilities for recipients from LRD were 94%, 83%, and 77% at 1, 5, and 7 years post-transplant, respectively.…”
Section: Effect Of Transplantation On Renal Functionmentioning
confidence: 99%
“…The incidence of living donation in our center is lower than that reported in the literature. In Europe, the LD transplantation accounts for around 40% of all pediatric KT . Van Huis et al reported a difference in the proportion of living kidney donation between children from the Netherlands and Belgium: 48% vs. 26%, respectively .…”
Section: Discussionmentioning
confidence: 99%